Pengaruh Pengalaman Merek, Kualitas Layanan, dan Kualitas Produk terhadap Loyalitas Pelanggan dengan Peran Mediasi Kepuasan Pelanggan - Sontia Asima Apriani Siregar; Puspita Chairun Nisa (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The highly competitive business marketing world requires entrepreneurs to find new ways to capture attention and maintain customer loyalty amidst an increasing market share and growing number of competitors. Therefore, the objective of this research is to understand how brand experience, service quality and product quality impact customer loyalty while considering the mediating role of customer satisfaction to contribute to the literature on these relationships. Data distribution to Kopi Kenangan customers rotating in Jakarta through a questionnaire of 110 respondents with the criteria of Kopi Kenangan customers aged 17-40 years who buy on the spot and drink Kopi Kenangan products directly at least 2 times in the last three months. This research utilized Structural Equation Modeling – Partial Least Square (SEM – PLS) analysis. The findings reveal that brand experience, service quality and product quality can enhance customer satisfaction and loyalty. Furthermore, the study also found that the relationship between brand experience, service quality and product quality with customer loyalty can be mediated by customer satisfaction. Therefore, this research emphasizes that companies need to improve customer experience, service quality, and product quality to achieve better customer satisfaction and loyalty, establishing a strong foundation for long-term competition.